On investigating the difference between outcomes obtained from nominal group technique and survey method - Islam, Rafikul (2015)
Nominal Group Technique (NGT) is a powerful group decision making tool. Many kinds of people – social science researchers, academicians, heads of business organizations, social activists have been using NGT to make decisions in group setting. Basically, NGT is a brainstorming method that generates a large number of ideas pertaining to a certain issue and also prioritizes those ideas through a voting scheme. Outcome of a nominal group (NG) session is a prioritized list of ideas. Normally, six to ten people participate in a NG session and they make the prioritized list together as a group through the aforementioned voting scheme. The present research is proposed to investigate the difference, if any, between the outcomes obtained from a nominal group session and a subsequent follow-up survey. Two experiments have been conducted in quick succession in order to compare the results of NGT study and the subsequent survey. It has been observed that, for both the experiments, the ranking of the ideas obtained in NGT and survey method is significantly close as supported by the associated rank correlation test. The findings of the present research reinforce the usefulness of NGT in terms of generating ideas and the reliability of the ranking that it generates.